Life table characteristics of Malaysian strain Aedes albopictus (Skuse) - Rozilawati H.,; Mohd Masri S.,; Tanaselvi K.,; Mohd Zahari TH.,; Zairi J.,; Nazni WA.,; Lee, HL (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2017)
The survival of a mosquito is the most important aspect that affects its ability as a pathogen transmitting vector, such as Aedes albopictus, which is a vector of chikungunya and dengue. Knowledge on mosquito life demographics is important in providing a foundation for a successful vector control programme. In this study, two strains of Ae. albopictus [Selangor (SEL) and Kuala Lumpur (KL)] were employed in order to determine the life demographics, including the development period, survival rate, mortality rate, and reproductive capability undercontrolled laboratory conditions. A cohort life table was developed based on the data collected. The complete life cycle period was inconsistent and ranged between 6 to 14 days. The males have a shorter survival period compared to the females. The percentage of females surviving and producing eggs has decreased across the gonotrophic cycle for both strains. A fluctuating pattern of oviposition among most of the females was observed throughout the gonotrophic cycle. The apparent mortality was highest at the embryogenesis stage than the other life stages across the gonotrophic cycle, with the pupae stage being recorded as the lowest mortality rate for both strains. Based on the demographic growth parameters calculated in this study, both strains showed favourable capability to be established in the laboratory. The data provided in this study can be used as a basic guideline on the population growth of the mosquito species and their capability as a pathogen vector.